Pengujian Kembali Volatilitas Kebijakan Trilemma Terhadap Variabel Makroekonomi di Indonesia - Moch. Syamsudin (Jurnal Ekonomi Akuntansi dan Manajemen, 2021)
The trilemma policy is a hypothesis stating a Mundell-Fleming macroeconomic development framework in which there is a state that cannot simultaneously choose three policies because it must sacrifice one policy so that the realization of policies that leads to economic stability is desired. The research aims to see the effect of the policy volatility on macroeconomic variables in Indonesia. The method used is the vector error correction model (VECM). The results show that the volatility of the trilemma policy adopted by Indonesia in the short and long term Affects the rate of economic growth and inflation. Economic shocks and uncertainties in the world economy externally affect macroeconomic variables. Viewing the results of forecasting for the trilemma policy and macroeconomic variables show that the inflation rate is so high and the level of economic openness is very low. This result recommends that there is a need for harmonization of policies undertaken by Bank Indonesia as the monetary authority and the government as a fiscal authority so as to achieve the level of financial stability that impacts on economic stability. Keywords: Trilemma Policy, Macroeconomics, Vector Error Correction Model (VECM), Forecasting